Views of Students and Lecturers on Module Development in Learning Listening Skills in Higher Education (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The aim of the initial research was to describe the potential that supports the implementation of listening skills using digital technology, namely the implementation of listening skills learning in the classroom, student characteristics, and the use of technology in developing teaching materials. The type of research used is descriptive. The research subject for lecturers in listening skills courses and students studying listening skills material in the Indonesian Language and Literature Education study program, Padang State University. The instruments used to collect data were observation sheets, questionnaire sheets, and listening skills test sheets. Data were analyzed using descriptive statistical analysis. The results of the preliminary research are: 1) The average score of students’ listening skills is still low so it needs to be improved. 2) The results of observations regarding the use of modules are still not utilized optimally, 3) The results of observations of digital teaching materials used by lecturers based on the LMS (Learning Management System) display conclude that not all lecturers use digital materials in the LMS, and 4) Results of student response questionnaires agree with the development of digital materials in the Learning Management System so that student learning outcomes improve. Based on the results of this preliminary study, it can be concluded that the modules currently used by lecturers in listening skills courses still need to be developed. The development of teaching materials is carried out by utilizing technology.